Composite Functions (Basic)
 1. f(x) = 3x + 5 Calculate f(2)A) 13B) 12C) 11D) 102. g(x) = x2 + 3x Calculate g(-3)A) 5B) -4C) 1D) 03. f(x) = 7x - 4 If f(x) = 10 Calculate xA) 3B) 2C) 1D) 04. h(x) = 2x3 + 5 If h(x) = 3 Calculate xA) -2B) -1C) 1D) 35. f(x) = 5x -2 Give a formula for f(2x)A) f(2x) = 5x -2B) f(2x) = 5x - 4C) f(2x) = 10x - 2D) f(2x) = 10x6. g(x) = 3x + 4 Give a formula for g(2x -3)A) g(2x -3) = 2x + 1B) g(2x -3) = 2x - 5C) g(2x -3) = 6x - 5D) g(2x -3) = 6x + 17. f(x) = 2x + 5 Using the domain of {-3, -2, -1, 0, 1, 2} Give the rangeA) {-3, -2, -1, 0, 1, 2}B) {-1, 1, 3, 5}C) {-1, 0, 1, 2, 3,5}D) {-1, 1, 3, 5, 7, 9}8. f(x) = x2 + x - 3 Using the domain of {-2, -1, 0, 1, 2} Give the rangeA) {-2, -1, 0, 1, 2}B) {-1, -3, 3}C) {-4, -3, -2, -1, 0}D) {-1, -3, 0}9. Using f(x) = 3x + 1 with a range of {1, 4, 7, 10} Give the domain that was usedA) {1, 2, 3, 4}B) {-1, 2, 5, 8}C) {0, 3, 6, 9}D) {0, 1, 2, 3}10. g(x) = 3x2 Give aformula for g(2x - 3)A) g(2x - 3) = 5x2 - 4x + 10B) g(2x - 3) = 4x2 - 12x + 9C) g(2x - 3) = 6x2 - 2x - 3D) g(2x - 3) = 12x2 - 36x + 27
Students who took this test also took :

Created with That Quiz — where a math practice test is always one click away.